Analysis Of Exchange Rates And Inflation On Gross Domestic Product In Indonesia - Fahrul Yusro Kudadiri; Kiki Hardiansyah Siregar; Dewi Mahrani Rangkuty (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the exchange rate and inflation of Gross Domestic Product in Indonesia. Where there is a Bound Variable, namely Gross Domestic Product and there are two Independent Variables, namely Exchange Rate and Inflation. This study uses secondary data by searching for data through the websites of BPS (Central Statistics Agency) and the World Bank. The data analysis model in this study uses multiple linear regression. The results of the study show that exchange rate variables and inflation have a significant effect on Gross Domestic Product in Indonesia.